2014
DOI: 10.2208/kaigan.70.i_1136
|View full text |Cite
|
Sign up to set email alerts
|

Particle Tracking Analysis of Larvae of Land Hermit Crab Coenobita brevimanus in Amitori Bay, Iriomote Island, Japan

Abstract: This study aims at investigating of dynamic states of larvae of land hermit crab Coenobita brevimanus in Amitori Bay, Iriomote Island, Japan from the perspective of numerical analysis. An ecological investigation of Coenobita brevimanus was conducted to provide input data for a numerical model. Reproduction of coastal currents in Amitori Bay was done using a coastal ocean current model CCM. The dynamic states of larvae of Coenobita brevimanus were examined using particle tracking analysis based on the ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The larvae of C. brevimanus and C. cavipes show smaller growth increments, but size of hatching larvae and pelagic duration of larvae are larger and shorter, respectively, for C. brevimanus, and smaller and longer, respectively, for C. cavipes (Hamasaki et al, 2015b). At the present study site, the numerical simulation using a biophysical model showed that about 10% of the larvae of C. brevimanus were retained near the spawning site after completion of the larval stage (Murakami et al, 2014). C. brevimanus with its shorter pelagic larval period may promote larval retention near the source population and strict constraint of the timing of spawning compared to the export strategy of C. cavipes.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The larvae of C. brevimanus and C. cavipes show smaller growth increments, but size of hatching larvae and pelagic duration of larvae are larger and shorter, respectively, for C. brevimanus, and smaller and longer, respectively, for C. cavipes (Hamasaki et al, 2015b). At the present study site, the numerical simulation using a biophysical model showed that about 10% of the larvae of C. brevimanus were retained near the spawning site after completion of the larval stage (Murakami et al, 2014). C. brevimanus with its shorter pelagic larval period may promote larval retention near the source population and strict constraint of the timing of spawning compared to the export strategy of C. cavipes.…”
Section: Discussionmentioning
confidence: 54%
“…This species shows a phenology and rhythm of spawning that is common in coenobitids of the Ryukyu Islands (Imafuku, 2001;Nakasone, 2001;Sato & Yoseda, 2008, 2009Doi et al, 2016Doi et al, , 2018a. The results of this study are valuable for understanding the population dynamics and structure as well as promoting conservation and management of the near-threatened C. brevimanus in this area along with previous findings from studies using numerical simulation of larval dispersal (Murakami et al, 2014;Doi et al, 2018b), spatiotemporal patterns of recruitment (Hamasaki et al, 2018) and genetic population network analysis with a sensitive genetic marker (Hamasaki et al, 2015a).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation